The LMS Guidebook : learning management systems demystified - Foreman, Steven D. (ATD Press, 2018)
Select, Implement, and Operate the Perfect LMS If you need to manage training and education programs for employees, customers, or students, you need an LMS. Don't waste time and money picking the wrong one. The LMS Guidebook gets to the core of what an LMS does and how it works. This book tackles the urgent challenges you will face when putting an LMS in place: Which features are must-haves? What standards should your LMS comply with to mesh with your other technology systems? How do you migrate existing learning data into your new LMS? How can you ensure an uneventful rollout? Not all LMS products will meet your needs. E-learning consultant Steve Foreman offers a broad view of the LMS categories and features so you can ask better questions of vendors and evaluate their products. He then turns to implementation and operation, offering in-depth guidance on how to establish appropriate standards, processes, and governance that will have your LMS running smoothly. Whether you're on the instructional or technical side of the LMS, you can make the job of selecting and managing one less painful by following the proven practices in this book.